Sexual behavior of Pecan tajacu (Cetartiodactyla: Tayassuidae) during periovulatory and early gestation periods - Bastos da Silva, Suleima do Socorro; Le Pendu, Yvonnick; Ohashi, Otavio Mitio; Oba, Eunice [UNESP]; Albuquerque, Natalia Inagaki de; Garcia, Alexandre Rossetto; Mayor, Pedro; Araujo Guimaraes, Diva Anelie de (Elsevier B.V., 2016)
The goal of this study was to describe the sexual behavior in female and male collared peccary. Twenty females and twelve males were monitored in familiar and non-familiar units for two 60 days periods. During both phases, we recorded 2747 sexual interactions initiated by 20 different females toward males and 4461 sexual interactions initiated by 12 males toward females. The frequency of sexual interactions initiated per female significantly increased from proestrus to estrus, and they were significantly more frequently courted. Females initiated olfactory inspections 15.42 times more and were mounted 22.6 times more during estrus than during proestrus. Nulliparous and primiparous females copulated only when exposed to non-parental males. After estrus, the frequency of sexual interactions received by females sharply decreased. One mating event was recorded during the first gestation week and 31 mountings were observed after the second week. In conclusion, the behavioral monitoring is a useful procedure for the recognition of estrus. Our results suggest that ovulation may be associated with the end of the estrus, which will support future work in assisted reproduction in this species. To promote good handling practices, females of reproductive age should be removed from their family unit of origin. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Behavior; Collared peccary; Estrus; Pregnancy; Reproduction